Evaluation of Different Capture Solutions for Ammonia Recovery in Suspended Gas Permeable Membrane Systems - María Soto-Herranz; Mercedes Sánchez-Báscones; Juan Manuel Antolín-Rodríguez; Pablo Martín-Ramos (Membranes, 2022)
Gas permeable membranes (GPM) are a promising technology for the capture and recovery of ammonia (NH3). The work presented herein assessed the impact of the capture solution and temperature on NH3 recovery for suspended GPM systems, evaluating at a laboratory scale the performance of eight different trapping solutions (water and sulfuric, phosphoric, nitric, carbonic, carbonic, acetic, citric, and maleic acids) at 25 and 2 °C. At 25 °C, the highest NH3 capture efficiency was achieved using strong acids (87% and 77% for sulfuric and nitric acid, respectively), followed by citric and phosphoric acid (65%) and water (62%). However, a remarkable improvement was observed for phosphoric acid (+15%), citric acid (+16%), maleic acid (+22%), and water (+12%) when the capture solution was at 2 °C. The economic analysis showed that water would be the cheapest option at any working temperature, with costs of 2.13 and 2.52 €/g N (vs. 3.33 and 3.43 €/g N for sulfuric acid) in the winter and summer scenarios, respectively. As for phosphoric and citric acid, they could be promising NH3 trapping solutions in the winter months, with associated costs of 3.20 and 3.96 €/g N, respectively. Based on capture performance and economic and environmental considerations, the reported findings support that water, phosphoric acid, and citric acid can be viable alternatives to the strong acids commonly used as NH3 adsorbents in these systems.